Visible, far-red, and near-infrared active unsymmetrical squaraine dyes based on extended conjugation within the polymethine framework for dye-sensitized solar cells - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Alkyl group wrapped visible, far-red, and NIR active unsymmetrical squaraine dyes with pi-extension in the polymethine framework-based AM4-AM7 have been designed, synthesized, and utilized as sensitizers for dye-sensitized solar cells. To extend the pi-conjugation within the polymethine framework, thiophene moieties have been incorporated between the donor and acceptor moieties. Absorption spectroscopic studies revealed that pi-extension with each -C & boxH;C- unit resulted similar to 100 nm of redshift in the charge transfer transition with the lambda(maximum) of 541, 643, 747, and 833 nm for AM4, AM5, AM6, and AM7 dyes, respectively, with the molar extinction coefficient of >10(5) M(-1)cm(-1). The pi-extended conjugation-based AM6 and AM7 dyes showed improved light-harvesting efficiency (LHE), where the AM7 dye showed an LHE of 386 nm at 60%. Electrochemical studies of AM dyes revealed that the HOMO energy level of the sensitizers has been modulated systematically. Further, pi-extension within the polymethine framework showed a dramatic effect on V-OC, J(SC), and device efficiency when move from visible active AM4 to far-red active to NIR active AM7 dyes. The DSSC efficiencies of 7.35, 5.18, 0.08, and 0.053% have been achieved with the I-/I-3(-) electrolyte (Z-50) for the AM4, AM5, AM6, and AM7 dyes, respectively. Further, AM4 dye has been cosensitized with AM5, AM6, and AM7 dyes, where AM4:AM5 (1:1) composition achieved the maximum efficiency of 8.12% with I-/I-3(-) electrolyte (Z-50) compared to the other cosensitization compositions.
Keywords: aggregation of dyes; DSSC device efficiency; light-harvesting efficiency; pi-extension; polymethine framework; squaraine dyes